Case Study : Nasken Coffee / Siti A'eshah Hanapi - Hanapi, Siti A'eshah (2021)
Based on entrepreneur of Nasken Coffee, they always faster actions that go beyond my imagination. They only start 1 branch on 27 December 2019 but in one year later the 10th branch has opened on 31 December 2020 in TROIKA, Kota Bharu. They have entrepreneurial competencies such as initiative, sees and acts on opportunities systematic planning and lastly selfconfident. They were inspired because can do that in short of time. Everyone know about this café and be number one of choice at this time. They not only focus in same menu but always update news menu. Hopefully, Nasken Coffee continues to develop and become a local brand that can compete with international brands and provide employment opportunities to Malaysians in general.